Effect of the Using of Think-Pair-Share Learning Model to Critical Thinking Skills, and Cognitive Learning Outcomes on Bacteriology Biology education Study Program Students Faculty of Teacher Training and Education, University of Mulawarman - Didimus Tanah Boleng (Universitas Sebelas Maret, 2015)
A quasi-experimental study was conducted in the Faculty of Teacher Training and Education, University of Mulawarman. The learning is applied in the classroom, is expected to provide the necessary learning outcomes by learners for their life. Critical thinking skills and cognitive learning outcomes, are needed by the students, to life in the 21st century. Nevertheless, critical thinking skills and cognitive learning outcomes is still volatile and tends to decline in the last three years, especially in subjects Bacteriology, the students of Biology Education Faculty of Teacher Training and Education, University of Mulawarman. Application of Think-Pair-Share (TPS) learning model, allowing students to interact with fellow students, and mutually reinforcing and complementary. The aims of research is to know: 1) the effect of the use of TPS learning model to critical thinking skills of students, 2)the effect of the use of TPS learning model to student’s bacteriological cognotive learning outcomes on bacteriological. The sample is the student of Biology Education who took a course of bacteriology in the second semester of academic year 2014/2015, which consists of thirty pairs. Sampling is by purposive sampling. Measuring tools such as critical thinking skills, and bacteriological cognitive learning outcomes test. The data analysis using the t test for paired samples. The t test results showed that for the critical thinking skills t value = 3.7, while t table with df = n1+n2-2 = 60-2 = 58, with α = 0.05 is 2.0; so t hitung˃t table. While for the cognitive learning bacteriology, t = 1.8, while t table with df = n1 + n2-2 = 60-2 = 58, with α = 0.05 is 2.0; so t hitung˂t table. Thus it can be said that there is the effect of the use of TPS learning model to critical thinking skills; but has no effect on the student’s bacteriological cognitive learning outcomes. Students have the opportunity to interact with fellow students, discuss, and complementary, in solving the problem of Bacteriology in the classes that implement TPS learning model.Keywords: Think-Pair-Share, Critical Thinking Skills, Cognitive Learning Outcomes, Bacteriology